Phenotypic spectrum of Costello syndrome individuals harboring the rare HRAS mutation p.Gly13Asp. Issue 5 (3rd April 2017) - Bertola, Débora; Buscarilli, Michelle; Stabley, Deborah L.; Baker, Laura; Doyle, Daniel; Bartholomew, Dennis W.; Sol‐Church, Katia; Gripp, Karen W.
Abstract : Costello syndrome is part of the RASopathies, a group of neurocardiofaciocutaneous syndromes caused by deregulation of the RAS mitogen‐activated protein kinase pathway. Heterozygous mutations in HRAS are responsible for Costello syndrome, with more than 80% of the patients harboring the specific p.Gly12Ser variant. These individuals show a homogeneous phenotype. The clinical characteristics of the Costello syndrome individuals harboring rarer HRAS mutations are less understood, due to the small number of reported cases. Here, we describe the phenotypic spectrum of five additional individuals with HRAS c.38G>A; p.Gly13Asp, including one with somatic mosaicism, and review five previously described cases. The facial and hair abnormalities of the HRAS p.Gly13Asp individuals differ from the typical pattern observed in those showing the common HRAS (p.Gly12Ser) mutation, with less coarse facial features and slow growing, sparse hair with abnormal texture, the latter resembling the pattern observed in Noonan syndrome‐like disorder with loose anagen hair and individuals harboring another amino acid substitution in HRAS (p.Gly13Cys). Although some individuals with HRAS p.Gly13Asp developed papillomata and vascular proliferation lesions, no malignant tumors occurred, similar to what was reported for individuals harboring the HRAS p.Gly13Cys. The fact that no malignant tumors were described in these individuals does not allow definitive conclusions about the risk for cancer development. It remains to be determined if substitutions of amino acid 13 in HRAS (p.Gly13Asp and p.Gly13Cys) increase the risk of tumor development.